The impact of swimming with traditional fins on the advancement of underwater sports in the region - Tolstopyatov I.A.; Redi E.V.; Lisovik A.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the influence of the advancement of the discipline of swimming with traditional fins on the growth of underwater sports in the Krasnoyarsk region. Methods and structure of the study. The examination of information from literary sources and methodological materials on underwater sports is conducted. Additionally, an analysis of the performance of athletes from the Krasnoyarsk Region in the period between 2021 and 2023 was performed. Results and conclusions. Since 2006, the sport of swimming with traditional fins has been incorporated into the program of scuba diving competitions. This was done to encourage athletes to engage in scuba diving and to expand the participation of countries in international competitions. It has been observed that in the past decade, there has been a substantial rise in the number of competitors in both Russia and abroad. A comparative study of the performance of athletes in the Krasnoyarsk Territory has revealed that the number of athletes participating in underwater sports has remained relatively stable over the past three years. The results of swimmers in the monolayer discipline have declined significantly over the past six years. Conversely, the results in swimming with classical fins have improved over the same period. Examining the evolution of underwater sports in the Krasnoyarsk Territory, it is evident that swimming with classical fins has contributed to the advancement of underwater sports in the region. However, coaches and the management of sports clubs should prioritize the disciplines of monolayer swimming, as there has been a noticeable decline in performance in these areas.